Analisis Ketepatan Kode External Cause Kasus Kecelakaan Lalu Lintas (KLL) Berdasarkan ICD-10 di RSUD dr. Soekardjo Kota Tasikmalaya Tahun 2014 - Amalia Wulandari; Ida Wahyuni (STIKes Persada Husada Indonesia, 2015)
Codefication Diagnosis should be done precisely, accurate and appropriate, considering the data diagnosis is authentic law evidence and data required in morbidity reports and insurance interests. External cause code used as secondary code to describe external causes of a disease. Coding of external cause in RSUD dr. Soekardjo not optimally implemented in accordance provision applicable based on Standard Operating Procedure (SOP). This research purpose to analyze the accuracy of external cause code four-digit and five-digit and the contributing factors. The type of this research is mix methodes. The method was used for 94 patients medical record documents, which were taken by total sampling and indepth interview with two informants. The data analysis is using univariate analysis using frequency distribution formula and also qualitative analysis. The results obtained the percentage of external cause four-digit code 24,5% accurate and 75,5 % not accurate. While the code external cause five-digit not found the accurate code. Accuracy and optimally coding in RSUD dr. Soekardjo influenced by diagnosis of external cause that is not written, procedures for coding, human resources and all aplication process. Suggestions for hospital should do socialization about the complete recording of the traffic accidents information according to the rules of coding and standard applications.